Kidney dysfunction in children with thalassemia - Lestari, Hertanti Indah; Rahmawati, Eka; Ayu, Dewi Rosariah; Fitriana, Eka Intan; Sari, Dian Puspita (Paediatrica Indonesiana, 2025)
Background Children with thalassemia are at risk for kidney dysfunction due to chronic anemia, frequent blood transfusions, iron retention, and use of iron chelating agents. Cystatin C, an endogenous marker for assessing estimated glomerular filtration rate (eGFR), a novel biomarker for the early detection of kidney failure, has been reported to be potentially superior to the commonly used serum creatinine. Objective To evaluate various creatinine- and cystatin C-based formulas for eGFR to detect kidney dysfunction in children with thalassemia. Methods This was a cross-sectional study on children (age <18 years) with thalassemia. Kidney dysfunction was defined as eGFR <90 mL/minute/1.73 m2. Hyperfiltration was defined as eGFR >150 ml/minute/1.73 m2. This study compared the proportion of kidney dysfunction as determined using various creatinine- and cystatin C-based eGFR formulas, comprising the creatinine-based Schwartz formula, the cystatin C-based Filler formula, the creatinine-cystatin C-based New CKID formula, and the creatinine-cystatin C-based Schwartz formula. Results The median age of the 152 study subjects was 11.0 (range 2.0-18.0) years. When using the creatinine-based Schwartz formula, none of the subjects had kidney dysfunction. Kidney dysfunction was found in 21.7% of subjects when using the cystatin C-based Filler formula, in 26.3% of subjects when using the creatinine-cystatin C-based (New CKID) formula, and 59.9% of subjects using the creatinine-cystatin C-based Schwartz formula. When using the creatinine-based Schwartz formula, 38.2% subjects experienced hyperfiltration no hyperfiltration was found by when using other eGFR formulas. There was low correlation between creatinine and cystatin C (r=0.195; P=0.016). There was only mild agreement in eGFR between the creatinine-based Schwartz formula and the cystatin C-based Filler formula (k=0.195; P<0.001). Conclusion The proportion of kidney dysfunction in children with thalassemia based on eGFR calculation using cystatin C- and creatinine-cystatin C-based formulas ranged from 21.7% to  59.9%. No kidney dysfunction was found using a creatinine-only-based eGFR formula, whereas hyperfiltration was a common finding. Hence, more than one parameter should be considered for early detection of kidney dysfunction in thalassemia.